Comparative Analysis of the Weibull Model and Observed Wind Data in the City of Floridablanca, Colombia - Hernández Arroyo, Emil; Córdoba Tuta, Edwin; García Sánchez, Gabriel (TECCIENCIA, 2018)
The main objective of this article is to evaluate the wind resource in the city of Floridablanca, Colombia. In Colombia, the supply of electrical energy comes mainly from hydroelectric mega-power stations, presenting generation problems in times of drought. The wind resource is an adequate alternative to diversify the electricity supply in the country. To analyze the characteristics of the wind, recorded measurements were carried out, every 15 minutes at a height of 30 m, throughout the year 2016, at a meteorological station located in Floridablanca, Colombia. In this study we present a statistical analysis of the wind characteristics in Floridablanca, Colombia, we applied a Weibull distribution of two parameters to model the wind speed and thus determine the wind potential. The average annual speed was 0.72 m/s with a standard deviation of 0.61 m/s. The monthly Weibull scale parameter varied from 0.52 m/s to 0.91 m/s, the monthly parameter varied from 0.98 to 1.37. The highest power density observed was 0.35 w/m2 in the months of February and August, the monthly average power density was 0.23 w/m2 which indicates a very poor wind potential considering that they are considered good wind potentials greater than 500 w/m2 . This study contributes to evaluate the wind potential of Floridablanca, Colombia, and can be used, methodologically, to quantify the wind potential with possibilities of generating electric power in any part of the country.